Metropolitan Access Network - Šarić, Slavko; Gorinšek-Halužan, Gabrijela; Matković, Ivan (Promet - Traffic&Transportation, 2003)
The optical fibre is the highest quality transmission mediumfor broadband services, and therefore the new access cablenetwork has to be realized to the greatest extent and as closeas possible to the subscriber by means of the optical fibre cables,in accordance with the possibilities of the telecommunicationoperator. The development of digital technology in commutations,supported by the increasingly powerful systems of processorcontrol, development of optical communications andtransport technologies in the framework of SDH concepts, arereflected on the access telecommunication networks of the urbanareas. Urban areas are the most profitable regions in telecommunications.In planning of urban optical networks the fact should betaken as a guideline that only a well-organised urban networkwill allow high quality of service provision of the leased cablesto the end points of business customers.Business customers have greater requirements for the networkreliability, flexibility and maintainability, for the sake ofundisturbed telecommunication traffic.The optical medium based technology- FITL (fiber in theloop), provides almost limitless upgrading of the system regardingthe transmission bandwidths, as well as adaptation to allthe future customers' requirements.Considering the increase in the price of installing the coppercables, the prices of electronics and optical components arecontinuously falling. The application of the optical medium isincreasing and becoming more cost-effective, and due to higherreliability of the optical transmission systems the maintenancecosts are reduced.